The Realization of the Fulfilment of the Children’s Sustenance Post-Divorce In Purworejo Religious Court in 2020-2021 - Yuniar, Meli Dwi; Sudarmaji, Waluyo (El-Usrah: Jurnal Hukum Keluarga, 2023)
Frequently, discordant married couples contemplate divorce as their final option for resolving household problems. Many do not realize that divorce is the beginning of the onset of new problems that affect not only married couples but also their offspring if they are already parents. This study seeks to find out the realization of the implementation of child support obligations after divorce at the Purworejo Religious Court with various factors that influence it. This investigation is limited to the years 2020 and 2021 in order to examine the most relevant cases, as the events are still relatively recent. This form of research employs a qualitative paradigm and is conducted in the field. This study's methodology employs a normative legal approach. On the basis of court records from the Purworejo Religious Court, researchers conducted direct observations and interviews with litigants. Even though the child's maintenance obligations have been stated in the decision of the Purworejo, the results of the study indicate that there are still many parents, particularly the father, who do not fulfill their responsibilities to provide a living for their children due to various factors, including lack of legal awareness, lack of awareness of the obligations of a father to provide for children, too involved parents in the household, social factors, and economic factors